Analysis of Sociocultural Changes in the Era of Industrial Revolution 4.0 on Mental Health in Teenage Women - Marwa Hasan Kadatua; Wildia Nanlohy; Melawati Wakano (GLOBAL HEALTH SCIENCE GROUP, 2024)
The era of industrial revolution 4.0 brought changes to the social life system of Indonesian society. The negative impact faced by teenagers with negative and irresponsible information can destroy the mentality of the younger generation in building the nation. This quantitative research uses a cross-sectional design. The population of this study was all 60 female students of SMA Negeri 11 Ambon who were selected using stratified random sampling techniques. The instrument used was a questionnaire. Bivariate analysis uses the chi-square test, and multiple linear regression to test the influence of independent variables on mental health. Bivariate analysis shows that the proportion of poor mental health without social isolation is 25 (41.7%) higher than the proportion of mental health with social isolation, namely 2 (3.3%). The results of bivariate analysis show that the proportion of poor mental health without Hedonism is 27 (45.0%) higher than the proportion of mental health with Hedonism, namely 0 (0%). The results of bivariate analysis show that the proportion of poor mental health without bullying is 25 (41.7%) higher than the proportion of mental health with bullying, namely 2 (3.3%). The results of the chi square test stated that the p-value was <0.05 between the variables social isolation (0.008), hedonism (0.000) and bullying (0.015) with mental health. The results of the multiple linear regression test found that hedonism had the most influence on mental health with a p value = 0.012. This value shows that there is a relationship between each variable (social isolation, hedonism and bullying with mental health. And hedonism as the variable that has the most influence on mental health.